2009
DOI: 10.1124/jpet.109.151654
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction: The Dietary Polyphenols trans-Resveratrol and Curcumin Selectively Bind Human CB1 Cannabinoid Receptors with Nanomolar Affinities and Function as Antagonists/Inverse Agonists

Abstract: The dietary polyphenols trans-resveratrol [5-[(1E)-2-(4-hydroxyphenyl)ethenyl]-1,3-benzenediol; found in red wine] and curcumin [1,7-bis(4-hydroxy-3-methoxyphenyl)-1E,6E-heptadiene-3,5-dione] (found in curry powders) exert anti-inflammatory and antioxidant effects via poorly defined mechanisms. It is interesting that cannabinoids, derived from the marijuana plant (Cannabis sativa), produce similar protective effects via CB1 and CB2 receptors. We examined whether trans-resveratrol, curcumin, and ASC-J9 [1,7-bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Recent studies indicated that curcumin selectively binds to CB-1 with nanomolar affinity and acts as an antagonist. When administered to mice repeatedly (2–10 mg/kg; twice daily; IP × 3 days), curcumin significantly reduced body weight in a dose-dependent manner (160). Thus, curcumin could work against obesity by reducing food intake and body weight.…”
Section: Effect Of Curcumin On Obesity and Metabolic Disorders In Animentioning
confidence: 99%
“…Recent studies indicated that curcumin selectively binds to CB-1 with nanomolar affinity and acts as an antagonist. When administered to mice repeatedly (2–10 mg/kg; twice daily; IP × 3 days), curcumin significantly reduced body weight in a dose-dependent manner (160). Thus, curcumin could work against obesity by reducing food intake and body weight.…”
Section: Effect Of Curcumin On Obesity and Metabolic Disorders In Animentioning
confidence: 99%
“…Of course, many other targets of resveratrol could contribute to its effects on body weight. One such target is the cannabinoid receptor CB1 [89], which can regulate body weight through food intake and appetite-independent mechanisms.…”
Section: Energy Expenditurementioning
confidence: 99%
“…In fact, the relationship between SIRT1 and AMPK is more complex, since each has been reported to influence the other [75, 99], however, activation of AMPK by resveratrol is at least partially independent of SIRT1 [74, 100]. Additional direct effects of resveratrol that could have important consequences in vivo include inhibition of kinases [101, 102], modulation of the estrogen receptor [103], the aryl hydrocarbon receptor [49], and a cannabinoid receptor [89], and inhibition of quinone reductase 2 [104], to name a few.…”
Section: “Off-target” Effects Of Resveratrolmentioning
confidence: 99%
“…In vitro studies showed that polyphenolic compounds could inhibit differentiation of adipocyte; also they inhibited lipolysis [25], lipogenesis [26] or intestinal lipid absorption [27] that they tend to lower weight. Polyphenolic compounds are inducers of fatty acid oxidation [26] or antagonist at cannabinoid receptors [28] and attenuate the inflammatory changes [29].…”
Section: Fig 1 Cinnamon In Ameliorating Metabolic Syndrome [24]mentioning
confidence: 99%